(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Boolean logic functions is possible to realize using collisions in bio-molecular quantum automata systems. Actin is a thin muscle filament consisting of two protein chains that mainly contribute to animal nervous system and eukaryotic cellular structure. Actin quantum cellular automata is also capable of quantum computation with help of qubits, if superposition of states is employed in the input and conducting moves using rules that are applicable to each of the actin molecules. In the present work, design of multiplexers like Multi bit multiplexer using actin filaments are proposed. For the sake of simplicity, classical bit representation is used to realize logic gates like AND gate, NOT gate and OR gate with the quantum automata. Finally these gates are utilized to design the proposed multiplexer. By comparing the efficiency of methodologies used in designing the circuits, optimized design for the proposed multiplexer is suggested